Health-related quality of life and functional disorders after diverticular surgery. (February 2022) - Segna, Daniel; Jaklin, Paul J.; Schnüriger, Beat; Misselwitz, Benjamin
Diverticulosis and diverticulitis are leading indications for colorectal surgery in Western countries. Abdominal pain, functional disorders, and low health-related quality of life (HRQoL) can limit the outcome of abdominal surgery even in the absence of complications. Therefore, we aimed to review current evidence on postoperative long-term outcomes including HRQoL, functional disorders, abdominal pain, and patients' satisfaction after diverticular surgery for diverticulosis/diverticulitis. We performed a PubMed database search (inception: 17 December 2020). Identified publications were screened and outcome parameters extracted. In summary, HRQoL increased after diverticular surgery in 9 out of 10 longitudinal cohort studies. Similarly, patients' satisfaction with treatment and their choice to undergo surgery was commonly reported as high or very good, as reported in eight studies. In a randomized control trial and retrospective cohort, elective diverticular surgery was superior to conservative treatment regarding HRQoL. In cross-sectional analyses, chronic abdominal pain and functional disorders including defaecation disorders or diarrhoea/obstipation were found in a relevant fraction of patients. Incontinence ranged from 5% to 25% with insufficient data for comparison before and after surgery. However, functional disorders did not result in decreased HRQoL in most studies, and no increase in functional disorders was observed after elective diverticular surgery in longitudinal analyses. We conclude that HRQoL among operated patients with diverticular disease improved in most studies after surgery. Functional disorders and postoperative abdominal pain can be present after elective diverticular surgery; however, no increase in functional disorders was observed in longitudinal studies. Functional disorders after diverticular surgery need to be carefully discussed with the patient before surgery and a careful clinical assessment before surgery including incontinence scoring should be considered.